Haemoglobin mass alterations in healthy humans following four‐day head‐down tilt bed rest. Issue 5 (24th March 2016) - Ryan, Benjamin J.; Goodrich, Jesse A.; Schmidt, Walter F.; Stothard, Ellen R.; Wright, Kenneth P.; Byrnes, William C.
Abstract : New Findings: What is the central question of this study? Is haemoglobin mass (Hbmass) decreased following 4 days of head‐down tilt bed rest (HDTBR), and does increased red blood cell (RBC) destruction mediate this adaptation? What is the main finding and its importance? Haemoglobin mass was increased immediately following HDTBR, before decreasing below baseline 5 days after return to normal living conditions. The transient increase in Hbmass might be the result of decreased RBC destruction, but it is also possible that spleen contraction after HDTBR contributed to this adaptation. Our data suggest that the decreased Hbmass 5 days following HDTBR resulted from decreased RBC production, not increased RBC destruction. Rapid decreases in haemoglobin mass (Hbmass) have been reported in healthy humans following spaceflight and descent from high altitude. It has been proposed that a selective increase in the destruction of young red blood cells (RBCs) mediates these decreases, but conclusive evidence demonstrating neocytolysis in humans is lacking. Based on the proposed triggers and time course of adaptation during spaceflight, we hypothesized that Hbmass would be reduced after 4 days of −6 deg head‐down tilt bed rest (HDTBR) and that this would be associated with evidence for increased RBC destruction. We assessed Hbmass in seven healthy, recreationally active men before (PRE), 5 h after (POST) and 5 days after (POST5) 4 days of HDTBR. The concentration of erythropoietin decreased from 7.1 ± 1.8 mIU ml −1 at PRE to 5.2 ± 2.8 mIU ml −1 at POST (mean ± SD; P  = 0.028). Contrary to our hypothesis, Hbmass was increased from 817 ± 135 g at PRE to 849 ± 141 g at POST ( P  = 0.014) before decreasing below PRE to 789 ± 139 g at POST5 ( P  = 0.027). From PRE to POST, the concentration of haptoglobin increased from 0.54 ± 0.32 to 0.68 ± 0.28 g l −1 ( P  = 0.013) and the concentration of bilirubin decreased from 0.50 ± 0.24 to 0.32 ± 0.11 mg dl −1 ( P  = 0.054), suggesting that decreased RBC destruction might have contributed to the increased Hbmass. However, it is possible that spleen contraction following HDTBR also played a role in the increase in Hbmass at POST, but as the transient increase in Hbmass was unexpected, we did not collect data that would provide direct evidence for or against spleen contraction. From PRE to POST5, the concentration of soluble transferrin receptor decreased from 20.7 ± 3.9 to 17.1 ± 3.3 nmol l −1 ( P  = 0.018) but the concentrations of ferritin, haptoglobin and bilirubin were not significantly altered, suggesting that the decrease in Hbmass was mediated by decreased RBC production rather than increased RBC destruction. Peak oxygen uptake decreased by 0.31 ± 0.16 l min −1 from PRE to POST ( P  = 2 × 10 −4 ) but was not significantly altered at POST5 compared with PRE. Overall, these findings indicate that 4 days of HDTBR does not increase RBC destruction and that re‐examination of the time course and mechanisms of Hbmass alterations following short‐term spaceflight and simulated microgravity is warranted. Abstract :